Aerodynamics of sport balls, badminton shuttlecock and javelin - Mehta, R. C. (Scholars Journal of Engineering and Technology, 2023)
The focus of the present chapter is to analysis aerodynamic forces and moment on sport balls, badminton shuttlecock and javelin. Lift force is analytically obtained employing Kutta-Joukowski theorem over a spinning sphere in an inviscid and incompressible flow. The inviscid flow analysis reveals that lift force is directly proportional to spinning which coincides with the experimental data of Bearman and Harvey. The lift force over the spinning sphere is less as compared to a rotating cylinder. The tangential velocity component on the surface of the spinning sphere is a cubic algebraic equation which has one real and two conjugate imaginary roots. Aerodynamic performance of feather and synthetic badminton shuttlecock is discussed in conjunction with experimental data. Available video images of a javelin trajectory are used to reconstruct its aerodynamic performance.